2019
DOI: 10.3928/01477447-20190118-03
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long Cephalomedullary Nails for Fixation of Stable Versus Unstable Intertrochanteric Femur Fractures at a Level 1 Trauma Center

Abstract: The purpose of this study was to compare failure and complication rates associated with short cephalomedullary nail vs long cephalomedullary nail fixation for stable vs unstable intertrochanteric femur fractures. This study included 201 adult patients with nonpathologic intertrochanteric femur fractures without subtrochanteric extension (OTA 31-A1.1-3, 31-A2.1-3, 31-A3.1-3) who were treated with a short cephalomedullary nail (n=70) or a long cephalomedullary nail (n=131) and had at least 6 months of follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Our results are in line with published results in both retrospective and prospective studies showing no difference in risk of reoperation and ipsilateral fractures when comparing long and short third generation cephalomedullary nails. [6][7][8][9]18 A higher risk of ipsilateral fracture were found using PFN compared to Gamma nail and when comparing gamma nails with sliding hip screw. 16,17 Those studies are from 2002 and therefore the Gamma Nails used were first and second generation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results are in line with published results in both retrospective and prospective studies showing no difference in risk of reoperation and ipsilateral fractures when comparing long and short third generation cephalomedullary nails. [6][7][8][9]18 A higher risk of ipsilateral fracture were found using PFN compared to Gamma nail and when comparing gamma nails with sliding hip screw. 16,17 Those studies are from 2002 and therefore the Gamma Nails used were first and second generation.…”
Section: Discussionmentioning
confidence: 98%
“…17 Later studies with second and third generations Gamma Nails show no difference in risk of reoperation and ipsilateral fractures when comparing long and short cephalomedullary nails. [6][7][8][9]18,19 In previous studies the comparison between short and long cephalomedullary nails focused on blood loss perioperative, time in theatre and cut out, but early and later studies do also compare complications for short and long cephalomedullary nails. A systematic review from 2017 20 comparing short and long intramedullary nails for OTA A1, A2 and A3 trochanteric fractures included 10 studies and their meta-analysis showed no difference in risk of complications, but supports the findings with reduced blood loss and time in theatre.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis, they found no difference in 1-year mortality [OR 1.20 (0.80; 1.79)] [9] . Hulet DA et al also believe that patients undergoing long and short intramedullary nails have no signi cant difference in their complications and failure rates during followup [10] . Although Hulet DA et al report that the use of short and long nails for patients with31-A1 and 31-A2 fractures is interchangeable [11] , we have found that long nails are recommended in patients with a large medullary cavity (diameter> 12mmBecause these patients belong to type 31-A2 fractures, short nail…”
Section: Discussionmentioning
confidence: 99%
“…Short nails have been shown to utilise approximately 20-30 min less operative time with less estimated blood loss in randomised trials, which is desirable for surgical efficiency and patient welfare [21]. Despite being a topic of recurrent interest, there is no proven association of increased risk of overall failure in comparison of long versus short IMN [12,13,[15][16][17]19,21], with further metanalysis showing no difference in nail failure for length [32]. However, great variability in fracture patterns prevails with bias towards longer nails used for more complex fractures.…”
Section: Nail Lengthmentioning
confidence: 99%
“…How the nail construct, most notably nail length, affects failure in unstable fractures is not well defined. Previous studies investigating nail length and failure have likely been underpowered [12][13][14][15][16][17] or use a variety of nailing systems with some already antiquated [18,19]. For randomized studies, adequately powering to failure as an outcome has not been performed [20], or a mixture of stable and unstable fracture patterns have been recruited without subgroup analysis [21].…”
Section: Introductionmentioning
confidence: 99%